Pembaharuan Undang-Undang Perkawinan Perihal Poligami Berdasarkan Hukum Perkawinan - Yudi Prihartanto Soleh (Jurnal Soshum Insentif, 2019)
Polygamy is one of the problems in marriage that is most highlighted by the people of Indonesia as well as considered controversial. The issue of polygamy is one of the issues regulated in Indonesian marriage law. In principle, marriage is a mental bond between a man and a woman as a husband and wife with the aim of forming a family. The establishment of the Marriage Law in Article 3, on the one hand applying the principle of monogamy, but in the next verse opened the opportunity for husbands to propose polygamy. Renewal of the Marriage Law can be interpreted as an effort and deed through a certain process with full seriousness committed by the government who have competence and authority in the development of Marriage Law in ways that have been specified based on the rules of law.